Presentation - Girón Perez, Mauel Iván (Revista Bio Ciencias, 2015)
The current issue of Revista Bio Ciencias is conformed by eight articles that address varied topics, such as the potential microbiological contamination in vegetables, plants and crops with medical and livestock prpoerties, biotechnological strategies in aquaculture, resistance to plagues and hydric balance in zones with high risk of margination.